A NEMZETÉPÍTÉS ÉS AZ ÖNÁLLÓ ÁLLAMISÁG MEGTEREMTÉSÉNEK DILEMMÁI A RENDSZERVÁLTÓ HORVÁTORSZÁGBAN - Bencze, Edit Lőrinczné dr. (Közép-Európai Közlemények, 2019)
According to Geoffrey Pridham Croatia such as other post-communist countries had to face multiple pressures. Dealing with the historical heritage, modernization, establishment of an independent and democratic state, security, economic transformation procedures were presented, in addition state‐, and nation‐building measures and the establishment of national identity as part of the political democratization were parallel processes and Croatia had to solve all these issues. Due to the extent and complexity of transformation and the whole nation-building process the consolidation took more than two decades. During this time Croatia passed through a period of redefine the country, the reinterpretation of its history and strong nationalist reawakening. The most significant factor shaping modern Croatian nationalist ideology was the concept of historical rights based on historical statehood traditions and claims to self-rule. This nationalist project and identity-building became a major guide in the creation of state procedure.